The Roles of Different Committees in ABET Accreditation Process for Engineering Programs - Mahmoud Saber Youssef (Universitas Diponegoro, 2022)
Different engineering degree programs are accredited by the Engineering Accreditation Commission (EAC). This commission is considered one among the four commissions of the Accreditation Board for Engineering and Technology (ABET). All programs seeking accreditation from the Engineering Accreditation Commission of ABET must demonstrate that they satisfy all of the eight General Criteria for Baccalaureate Level Programs. Therefore, to execute these different ABET criteria and guidelines, any engineering program must establish different committees. In this paper, we nominate different committees and clearly mention their tasks in details. Moreover, the time schedules for the different activities of these committees during both fall and spring semesters are proposed. Another contribution of this article is to present a robust scheme for continuous improvement process. The roles of the contribution of some program committees in this scheme are described clearly. Therefore, the authors thought that the proposed scheme can serve as a strong reference in continuous improvement process for all engineering programs.